2005
DOI: 10.1007/s11099-005-0033-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characteristics of Hordeum, Triticum, Rumex, and Trifolium species at contrasting altitudes

Abstract: Photosynthetic characteristics were compared between plants of low altitude (LA) grown at LA (Palampur; 1 300 m) and at high altitude, HA (Kibber; 4 200 m), and plants naturally occurring at different altitudes (Palampur, 1 300 m; Palchan, 2 250 m; and Marhi, 3 250 m). Net photosynthetic rate (P N ) was not significantly different between altitudes. However, the slopes of the curve relating P N to intercellular CO 2 concentration (C i ) were higher in plants at Palchan, Marhi, and Kibber compared to those at P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
2
25
2
Order By: Relevance
“…Contrary to the results of this study, Kumar et al (2005) reported no significant difference in P n of wheat and barley between altitudes 1300 m and 4200 m above sea level. They suggested that higher efficiency of carbon uptake at higher altitude resulted in similar P n at both altitudes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the results of this study, Kumar et al (2005) reported no significant difference in P n of wheat and barley between altitudes 1300 m and 4200 m above sea level. They suggested that higher efficiency of carbon uptake at higher altitude resulted in similar P n at both altitudes.…”
Section: Discussioncontrasting
confidence: 99%
“…The values of stomatal conductance at low altitude were 0.14-0.17 mol m -2 s -1 , which were relatively lower compared with the values in this study at 0.21-0.69 mol m -2 s -1 and other studies at 0.1-1 mol m -2 s -1 (Reynolds et al, 2000;Martínez-Carrasco et al, 2005). This suggests environmental stresses were at low altitude in the experiment by Kumar et al (2005), leading to lower stomatal conductance and P n at low altitude than at high altitude. In this study, the values of stomatal conductance in all experiments were similar to other studies (Reynolds et al, 2000;Martínez-Carrasco et al, 2005), and stomatal conductance showed no difference between altitudes.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Mountain plants evolved in response to their particular altitude environment differ in physiological response to the respective ecotypes from lowland areas (Billings et al 1961, Hiesey et al 1971, Mächler et al 1977, Körner and Diemer 1987, Cordell et al 1998, Hovenden and Schimanski 2000, Hovenden and Schoor 2003, Kumar et al 2005. However, there is little information on altitude related changes in enzymatic activities related to carbon metabolism except for enzymes such as ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBPCO).…”
mentioning
confidence: 99%